2023
DOI: 10.1587/transinf.2022mpp0001
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of Package Management Issues via Stack Overflow

Abstract: The package manager (PM) is crucial to most technology stacks, acting as a broker to ensure that a verified dependency package is correctly installed, configured, or removed from an application. Diversity in technology stacks has led to dozens of PMs with various features. While our recent study indicates that package management features of PM are related to end-user experiences, it is unclear what those issues are and what information is required to resolve them. In this paper, we have investigated PM issues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 30 publications
(36 reference statements)
1
5
0
Order By: Relevance
“…As a whole, tweets belonging to the package management category, including topics such as usage scenarios, configurations, feature information, bug reports, software comparisons, and dependencies, were most prevalent (i.e., 58%). This finding is consistent with our previous studies on software ecosystem issues 13,14 . The findings indicate that developers are using Twitter to filter and curate information about package management activities associated with the npm ecosystem.…”
Section: Topic Of Tweet (Rq 1 ): What Are the Main Topics Of Interest...supporting
confidence: 94%
See 4 more Smart Citations
“…As a whole, tweets belonging to the package management category, including topics such as usage scenarios, configurations, feature information, bug reports, software comparisons, and dependencies, were most prevalent (i.e., 58%). This finding is consistent with our previous studies on software ecosystem issues 13,14 . The findings indicate that developers are using Twitter to filter and curate information about package management activities associated with the npm ecosystem.…”
Section: Topic Of Tweet (Rq 1 ): What Are the Main Topics Of Interest...supporting
confidence: 94%
“…These prior studies show that Twitter posts are useful to understand software developers' challenges. In our previous empirical studies, we looked at the software packaging ecosystem-related discussions by developers on question-and-answering sites and found that package management issues are the biggest challenge [13][14][15] . However, no study has been conducted so far to examine the tweets shared by developers to reveal the challenges associated with using the software packaging ecosystem and how they differ from question-and-answer sites.…”
Section: Studies On Communication Channelsmentioning
confidence: 99%
See 3 more Smart Citations